Sistem Informasi Pelayanan Surat Menyurat Di Kelurahan Desa Sriwijaya Lampung Tengah - Andronias Siregar; Arief Satriansyah; Rachmat Hidayat; Maya Septa Wijaya (LPPM STT Terpadu Nurul Fikri, 2023)
Information technology has progressed quite rapidly, and more and more years are increasingly developing technology worldwide. Information technology greatly benefits the world government by creating village websites and building computer-based information systems. With information technology, everyone can process and access data and information they want to convey to the whole community through the website so that everyone can access it easily without having to come and ask the staff or person concerned. The problem with the mailing service in the Village of Sriwijaya Village, Central Lampung, where the process of making letters is still done manually, there are still writing errors. The purpose of creating this correspondence information system is to overcome existing problems and help employees and staff make it easier to update village and community development information by easily accessing this information; with this system, staff can also improve skills in information technology. The method used by the waterfall in making this information system includes making correspondence and information systems in the Sriwijaya village, using the PHP program and MYSQL database. The results of this study are a web-based correspondence information system that is very helpful for community services in making certificates, KK, KTP, SKU, and more quickly and saves time.